Učiteljski kadar na pragu Istoka i Zapada / Teaching Personnel on the Threshold of East and West - Smajić, Ramiza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
This text is a review of a book Mujo Koštić's Lexicon of Elementary School Teachers in Sarajevo from 1878 to 1918, Sarajevo: National and University Library of Bosnia and Herzegovina, 2020.